PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPAS MELALUI MODEL PEMBELAJARAN LEARNING STARTS WITH A QUESTION PADA SISWA SEKOLAH DASAR - itaa, Juita; Nadrah; Sultan, Ana Dhiqfaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research (CAR) aims to improve students’ learning activities and learning outcomes in IPAS through the implementation of the Learning Starts With A Question (LSQ) model among 21 fifth-grade students at UPT SPF SD Inpres Bontomanai. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation and tests, then analyzed using descriptive quantitative methods. The results show that students’ learning activities improved from a moderate category in Cycle I to a high category in Cycle II, while learning outcomes also increased and met the predetermined mastery criteria. Therefore, the Learning Starts With A Question (LSQ) model is effective in improving students’ learning activities and outcomes.